Pharmacogenomics considerations in the control of hypertension. (November 2015) - Lupoli, Sara; Salvi, Erika; Barcella, Matteo; Barlassina, Cristina
The response to antihypertensive therapy is very heterogeneous and the need by the physicians to account for it has driven much interest in pharmacogenomics of antihypertensive drugs. The Human Genome Project and the initiatives in genomics that followed, generated a huge number of genetic data that furnished the tools to explore the genotype–phenotype association in candidate genes and at genome-wide level. In spite of the efforts and the great number of publications, pharmacogenomics of antihypertensive drugs is far from being used in clinical practice. In this review, we analyze the main findings available in PubMed from 2010 to 2015, in relation to the major classes of antihypertensive drugs. We also describe a new Phase II drug that targets two specific hypertension predisposing mechanisms.